Pengaruh Permainan Dore Modifikasi Terhadap Kemampuan Motorik Kasar Anak Usia 5-6 Tahun di Taman Kanak-kanak Aisyiyah 5 Padang - Syadillah Lovita; Indra Yeni (Global Action and Education for Society, 2024)
The aim of this research is to find out how much influence the modified Dore game has on the gross motor skills of children aged 5-6 years at Aisyiyah 5 Padang Kindergarten. This research uses a quantitative approach in the form of a Quasi Experiment. The population of this study was 26 children at Aisyiyah 5 Padang Kindergarten. The sampling technique was Cluster Sampling for children in classes B4 and B5, each with a total of 13 children. Data collection techniques use observation, interviews and documentation techniques. Data analysis techniques use normality tests, homogeneity tests, hypothesis tests, data collection tools use statement sheets. The data was processed with a difference test (t-test) using the SPSS 25.0 application. Based on data analysis, the average pre-test and post-test scores for the experimental group were 17.92 and 22.31 respectively. In contrast, in the control group, the average pre-test and post-test scores were 17.46 and 20.77, respectively. In the independent sample t test, the sig (2-tailed) value was obtained, namely 0.175. Thus, it can be concluded that there is a significant influence in the modified dore game on the gross motor skills of children aged 5-6 years at the Aisyiyah 5 Padang Kindergarten for the 2023/2024 academic year.